Provisional analytical procedures for mapping MFS, their socio-ecological context, and system performance - Le, Quang Bao (International Center for Agricultural Research in the Dry Areas, 2022)
A methodological approach for mapping mixed farming systems (MFS) and typologies at national and sub-national levels is proposed and described, with concrete system-based analytical pathway and suggested data sources. The approach is under developing, will be finalized and adaptively used for MFS mapping in the target countries of the CGIAR Initiative on Sustainable Intensification of MFS (SI-MFS) in 2023.